The second International Symposium on Fungal Stress: ISFUS - Alder-Rangel, Alene; Bailao, Alexandre M.; Cunha, Anderson F. da; Soares, Celia M. A.; Wang, Chengshu; Bonatto, Diego; Dadachova, Ekaterina; Hakalehto, Elias; Eleutherio, Elis C. A.; Fernandes, Everton K. K.; Gadd, Geoffrey M.; Braus, Gerhard H.; et al. (Elsevier B.V., 2018)
The topic of 'fungal stress' is central to many important disciplines, including medical mycology, chronobiology, plant and insect pathology, industrial microbiology, material sciences, and astrobiology. The International Symposium on Fungal Stress (ISFUS) brought together researchers, who study fungal stress in a variety of fields. The second ISFUS was held in May 8-11 2017 in Goiania, Goias, Brazil and hosted by the Instituto de Patologia Tropical e Satide Pablica at the Universidade Federal de Goias. It was supported by grants from CAPES and FAPEG. Twenty-seven speakers from 15 countries presented their research related to fungal stress biology. The Symposium was divided into seven topics: 1. Fungal biology in extreme environments; 2. Stress mechanisms and responses in fungi: molecular biology, biochemistry, biophysics, and cellular biology; 3. Fungal photobiology in the context of stress; 4. Role of stress in fungal pathogenesis; 5. Fungal stress and bioremediation; 6. Fungal stress in agriculture and forestry; and 7. Fungal stress in industrial applications. This article provides an overview of the science presented and discussed at ISFUS-2017. (C) 2017 British Mycological Society. Published by Elsevier Ltd. All rights reserved.
Keywords: Agricultural mycology; Forest mycology; Fungal stress mechanisms and responses; Industrial mycology; Medical mycology